Pelatihan Pembuatan Video Pembelajaran Menggunakan OBS Studio bagi Guru Sekolah Mandiri Palembang: Training on Making Learning Videos Using OBS Studio for Teachers at Sekolah Mandiri Palembang - Yuniansyah, Yuniansyah; Aprizal, Yarza; Aribowo, Muhammad Fajar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This training aims to enhance teachers' skills in using technology, particularly the Open Broadcaster Software (OBS) Studio application, to produce effective and engaging learning videos for students. The methods applied in this training include presentations, demonstrations, and hands-on practice with the OBS Studio application to create learning videos. The outcome of this training is learning videos designed by the teachers. Based on the assessment of the videos created by the teachers and the analysis of the questionnaire data, it can be concluded that this training has improved the teachers' ability to create learning videos using the OBS Studio application, and the teachers were highly satisfied with the content and delivery of the training materials.